2005
DOI: 10.1038/sj.bjc.6602338
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antiangiogenic activity of AW464 (NSC 706704), a novel thioredoxin inhibitor: an in vitro study

Abstract: AW464 (NSC 706704) is a novel benzothiazole substituted quinol compound active against colon, renal and certain breast cancer cell lines. NCI COMPARE analysis indicates possible interaction with thioredoxin/thioredoxin reductase, which is upregulated under hypoxia. Through activity on HIF1a, VEGF levels are regulated and angiogenesis controlled. A thioredoxin inhibitor could therefore exhibit enhanced hypoxic toxicity and indirect antiangiogenic effects. In vitro experiments were performed on colorectal and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 37 publications
1
45
1
Order By: Relevance
“…Both compounds inhibited VEGF expression at subtoxic concentrations in hypoxic breast and melanoma cell lines and pVHL mutant renal cell lines, with AJM290 being the more potent compound. Studies carried out by Mukherjee et al showed that hypoxia reduced the IC 50 of AW464 by f5-fold in all colorectal cancer cell lines tested (35). However, we saw no changes in IC 50 between hypoxic and normoxic cells and pVHL mutant and stable pVHL-transfected cells following 16 or 48 hours of treatment with AJM290 or AW464.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Both compounds inhibited VEGF expression at subtoxic concentrations in hypoxic breast and melanoma cell lines and pVHL mutant renal cell lines, with AJM290 being the more potent compound. Studies carried out by Mukherjee et al showed that hypoxia reduced the IC 50 of AW464 by f5-fold in all colorectal cancer cell lines tested (35). However, we saw no changes in IC 50 between hypoxic and normoxic cells and pVHL mutant and stable pVHL-transfected cells following 16 or 48 hours of treatment with AJM290 or AW464.…”
Section: Discussioncontrasting
confidence: 47%
“…However, we saw no changes in IC 50 between hypoxic and normoxic cells and pVHL mutant and stable pVHL-transfected cells following 16 or 48 hours of treatment with AJM290 or AW464. The difference in results could be due to the cell lines used (35).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Apparently, this TR1 dichotomy requires the thioredoxin pathway, due to the many targets of this protein. This hypothesis could explain both the potent cancer prevention activity of dietary selenium (19,20) and the potent antitumor activity of drugs that target TR1 (7)(8)(9)(10)(11)(12)(13). Most importantly, this study provides a foundation to explain literature data on the role of TR1 in cancer and establishes this enzyme as a prime target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…AW464 has anti-proliferative activity on tumor cell lines and endothelial cells in vitro, but not fibroblasts, with IC 50 value of 0.5 ”M (Mukherjee et al 2005).…”
Section: Inhibitors Of Trxmentioning
confidence: 99%